A Probabilistic Study of Duration of Post-partum Amenorrhoea in rural Uttar Pradesh - Maurya, Ravikant; Pratap Singh, Brijesh; Kumar Tiwari, Abhay; Singh, Anuj (Brazilian Journal of Biometrics, 2025)
The present study introduces a model designed to assess the distribution of post-partum amenorrhea durations through a mixture of two Weibull distribution. The suitability of the model is evaluated by analysing data extracted from a research project funded by the Indian Council for Medical Research (ICMR). The analysis shows that breastfeeding plays a significant role in how long PPA lasts, with longer breastfeeding linked to longer periods without menstruation. Additionally, women with lower socio-economic status and poorer nutrition tend to have longer PPA durations. Using the two Weibull distributions helps capture the different patterns of PPA, providing a detailed understanding of this important health issue.